An analysis of total phosphorus dispersion in lake used as a municipal water supply - LIMA, Romulo Correa (Academia Brasileira de Ciências, 2017)
In Belém city is located the potable water supply system of its metropolitan area, which includes, in addition to this city, four more municipalities. In this water supply complex is the Água Preta lake, which serves as a reservoir for the water pumped from the Guamá river. Due to the great importance of this lake for this system, several works have been devoted to its study, from the monitoring of the quality of its waters to its hydrodynamic modeling. This paper presents the results obtained by computer simulation of the phosphorus dispersion within this reservoir by the numerical solution of two-dimensional equation of advection-diffusion-reaction by the method θ/SUPG. Comparing these results with data concentration of total phosphorus collected from November 2008 to October 2009 and from satellite photos show that the biggest polluters of the water of this lake are the domestic sewage dumps from the population living in its vicinity. The results obtained indicate the need for more information for more precise quantitative analysis. However, they show that the phosphorus brought by the Guamá river water is consumed in an area adjacent to the canal that carries this water into the lake. Phosphorus deposits in the lake bottom should be monitored to verify their behavior, thus preventing the quality of water maintained therein.